Growth dynamics and disturbances along the last four centuries in the Prosopis caldenia woodlands of the Argentinean pampas - Velasco Sastre, Teresa (2018)
Fil: Velasco Sastre, Teresa. Universidad Nacional de San Luis. Departamento de Ciencias Agropecuarias; Argentina.